Ozone therapy ameliorates paraquat-induced lung injury in rats. (December 2014) - Kaldirim, Umit; Uysal, Bulent; Yuksel, Ramazan; Macit, Enis; Eyi, Yusuf E; Toygar, Mehmet; Tuncer, Salim K; Ardic, Sukru; Arziman, Ibrahim; Aydin, Ibrahim; Oztas, Yesim; Karslioglu, Yildirim; et al.
Paraquat (PQ) overdose can cause acute lung injury and death. Ozone therapy (OT) was previously demonstrated to alleviate inflammation and necrosis in various pathologies. We therefore hypothesized that OT has ameliorative and preventive effects on PQ-induced lung damage due to anti-inflammatory and antioxidants properties. Sprague-Dawley rats ( n = 24) were separated into three groups: sham, PQ, and PQ+OT groups. 15 mg/kg PQ was administered intraperitoneally in PQ and PQ+OT groups to induce experimental lung injury. One hour after PQ treatment, PQ+OT group was administered a single dose of ozone–oxygen mixture (1 mg/kg/day) by intraperitoneal route for four consecutive days. The animals were sacrificed on fifth day after PQ administration. Blood samples and lung tissues were collected to evaluate the inflammatory processes, antioxidant defense and pulmonary damage. Serum lactate dehydrogenase (LDH) and neopterin levels, tissue oxidative stress parameters, total TGF-β1 levels, and histological injury scores in PQ+OT group were significantly lower than PQ group ( P <0.05, PQ vs. PQ+OT). Total antioxidant capacity in PQ+OT group was significantly higher than PQ group ( P < 0.05, PQ+OT vs. PQ). These findings suggest that outcome in PQ-induced lung injury may be improved by using OT as an adjuvant therapy.